Initial Experience in Transvenous Implantation of a Left Ventricular Lead With a Novel Venogram Balloon Catheter - Duan, Jiangbo; Yang, Dandan; He, Jinshan; Li, Xuebin; Wang, Long; Wu, Cuncao; Li, Ding; Ze, Feng; Yuan, Cuizhen; Zhou, Jingliang; Zhou, Xu (Frontiers in Cardiovascular Medicine, 2022)
Aim The most challenging and time-consuming stage of cardiac resynchronization therapy (CRT) device implantation is coronary sinus (CS) cannulation and left ventricular epicardial electrode implantation. This paper reports the initial clinical experience of CS cannulation and left ventricular lead implantation guided by a novel venogram balloon catheter (Lee’s venogram balloon catheter). Methods and Results Consecutive patients eligible for CRT were deemed suitable for this novel venogram balloon catheter. Parameters such as left ventricular lead implantation time, procedure time, and fluoroscopy time were recorded. CS cannulation with LV lead implantation guided by Lee’s venogram balloon catheter was successful in all 5 patients, including 4 challenging cases. The total fluoroscopy and procedural durations were 5.0 ± 3.0 and 57.4 ± 12.5 min, respectively. No adverse catheter-related events occurred during the procedures. Conclusion This initial study of an innovative venogram balloon catheter demonstrated that it greatly facilitated CS cannulation and successful LV lead placement in all patients undergoing CRT system implantation. This significantly shortened the learning curve and showed a decrease in left ventricular lead implantation time, procedure time, and fluoroscopy time.